2021
DOI: 10.3389/frobt.2021.612964
|View full text |Cite
|
Sign up to set email alerts
|

Telerobotic Operation of Intensive Care Unit Ventilators

Abstract: Since the first reports of a novel coronavirus (SARS-CoV-2) in December 2019, over 33 million people have been infected worldwide and approximately 1 million people worldwide have died from the disease caused by this virus, COVID-19. In the United States alone, there have been approximately 7 million cases and over 200,000 deaths. This outbreak has placed an enormous strain on healthcare systems and workers. Severe cases require hospital care, and 8.5% of patients require mechanical ventilation in an intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The application of robotics in the medical field is extensive, encompassing myriad functions and scenarios, rendering their precise classification a formidable task. Multimedia Appendix 2 [ 6 , 18 - 90 ], which is neither exclusive nor exhaustive, summarizes the representative research groups and commercial suppliers to provide readers with a panoramic view of the field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of robotics in the medical field is extensive, encompassing myriad functions and scenarios, rendering their precise classification a formidable task. Multimedia Appendix 2 [ 6 , 18 - 90 ], which is neither exclusive nor exhaustive, summarizes the representative research groups and commercial suppliers to provide readers with a panoramic view of the field.…”
Section: Resultsmentioning
confidence: 99%
“…Computer vision tasks that enable an intuitive user interface and accurate robot control are executed on the master console. The system was initially developed and deployed for the most popular touch screen–controlled ventilator at Johns Hopkins Hospital, the Maquet Servo-u (Getinge AB) [ 18 ]. Different from the traditional ventilators in most ICUs, the robot performs remote control and monitoring outside the ICU room through the network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sawyer (Rethink Robotics GmbH) [ 43 ], a 7-axis robot with flexible joints and a camera, could successfully perform a variety of COVID-19 health care tasks: intravenous pump device continuation, ventilator knob adjustment, ICU monitor silencing, oxygen knob adjustment, and call button deactivation. Vagvolgyi et al [ 44 ] demonstrated the use of a telerobotic cartesian system to allow the adjustment of ventilator settings from outside the ICU. Similarly, this was feasible in a simulated ICU environment and specifically saved 59.8% of the time (a decrease from 271 seconds to 109seconds).…”
Section: Discussionmentioning
confidence: 99%
“…"According to the physiological structure of the human body, doctors have great limitations in terms of the accuracy, stability, fatigue resistance and radiation resistance of the operation, which are the advantages of robots" [5]. The so-called service robots are mostly simple, low-cost and controlled by touch screens [6,7]. It also has unique advantages in medical treatment, such as identification and avoidance ability and intelligent human-computer interaction interface, so as to be safe and radiation-free and adapt to the human spirit [5].…”
Section: Introductionmentioning
confidence: 99%